Society of Vascular and Interventional Neurology Standards and Parameters for Guideline Development and Publication. Issue 1 (17th November 2021) - Castonguay, Alicia C.; de Havenon, Adam; Leslie‐Mazwi, Thabele M.; Kenmuir, Cynthia; Sheth, Sunil A.; Asif, Kaiz S.; Nguyen, Thanh N.; Janardhan, Vallabh; Mansour, Ossama Y.; Novakovic, Robin; Hassan, Ameer E.; Liebeskind, David S.; et al.
Abstract : Background: As much of the scope of neurointerventional practice falls outside data covered by existing randomized clinical trials, and, as a result, may have failed to enter into existing guidelines, an evidence‐based framework for guideline and standards development is needed. We establish an evidence‐based framework to guide all subsequent guidelines and brief practice updates produced by the Society of Vascular and Interventional Neurology (SVIN). Methods: The SVIN formed the Guidelines and Practice Parameters committee to develop the structure and procedures for guidelines and brief practice updates. Results: In this article, the Guidelines and Practice Parameters committee has outlined the process by which the guidelines will be created and approved by the SVIN. Additionally, the Guidelines and Practice Parameters committee has adopted the American College of Cardiology/American Heart Association framework of Class of Recommendation and Level of Evidence. A unique, additional separation of the Expert Opinion endorsement category has been developed when high‐quality evidence does not exist at the time of the publication. Conclusions: The SVIN has developed an evidence‐based framework for all guideline statements and brief practice updates. The SVIN guidelines and brief practice updates will guide clinicians in the field of interventional neurology to improve and standardize patient care.